Allelopathic potential of root and leaf aqueous extracts of invasive alien plant species, Cryptostegia grandiflora, on germination and seedling growth of Linum usitatissimum and Guizotia abyssinica - Seifu, Amare; Lulekal, Ermias; Demissew, Sebsebe; Woldu, Zerihun (Frontiers in Forests and Global Change, 2023)
C.grandiflora has been termed the worst invasive alien plant species. However, its allelopathic potential has not been studied yet. The goal of this research was to study the allelopathic potential of C. grandiflora on the germination and seedling growth of L. usitatissimum and G. abyssinica. Plant specimens and samples of C. grandiflora were collected from Minjar-Shenkora district, North Shewa Zone, Ethiopia. An experimental investigation was conducted to check the impact of its leaf and root extracts on the growth and germination parameters of the indicated test plant species. The root and leaf samples were extracted with water and methanol (99.85%).Twenty-five grams of leaf and root samples were steeped separately in 250 ml of each of the specified solvents to make the stock solutions. The experiment was conducted in 9-cm-diameter petri-dishes and laid-out in completely random designs, replicated thrice with five blocks, each block representing a different concentration of extract (25%, 50%, 75%, and 100%) and control. Twenty-five seeds of each test plant were placed in a petri-dish along with five ml of each extract. Differences between treatments were evaluated using one-way-ANOVA and Tukey’s Honestly Significant Difference (HSD) Test. Results revealed that the inhibitory effect of water extracts' of roots and leaves sample were concentration-dependent. With leaf extracts as opposed to root, the inhibitory effect was more pronounced. Hence, when L. usitatissimum seeds treated with 100% concentration of water extracts from leaf samples of C. grandiflora germination-percentage, seedlings dry-weight, plumule and radicle length were reduced by 80%, 79.3%, 73.6% and 79.4% respectively compared to the control. The above parameters were also dropped considerably when G. abyssinica seeds were treated with the indicated concentrations. Conversely, germination of seeds from both test plant species was entirely inhibited in methanol extracts. From this study, it can be deduced that these invasive plant extracts have herbicidal properties. Further phytochemical and molecular study is recommended to identify the active ingredients of C. grandiflora and determine their characteristics. Besides, the integration of identified allelopathic substances as a tool in the management of invasive species is proposed as an environment-friendly option to lessen the deterioration of ecosystem-services.